Palaeoenvironments and landscape diversity in Egypt during the Last Interglacial and its implications on the dispersal of Homo sapiens. Issue 4 (1st January 2022) - Henselowsky, Felix; Kindermann, Karin; Willmes, Christian; Lammerich-Long, Dorothee; Bareth, Georg; Bubenzer, Olaf
ABSTRACT: The Last Interglacial period is important for the spread of humans from Africa to Eurasia. Significant wetter climatic conditions allowed humans to live in the present-day arid landscape in Northeastern Africa. However, not only the environment but also other parameters, such as the topography and the availability of good raw material sources, impact past human behaviour. Our mapping with the integration of archaeological sites and environmental archives clarifies regional differences and similarities across Egypt. The Eastern Desert is characterized by a small structured landscape with an above-average occurrence of eligible raw material and it differs from the more homogeneous landscape of the Western Desert with its large palaeo-lakes. The given map allows a more distinct evaluation of regional variabilities for Out-of-Africa's northern migration route as a complex intermediate scale between a global and local approach to human-environment relations.